Association between knowledge and attitudes towards pediatric obstructive sleep apnea and dental specialty - Díaz-Díaz, María Fernanda (2023)
Objective: To associate the knowledge and attitudes about Pediatric Obstructive Sleep Apnea (POSA) with the specialty of dentists in Metropolitan Lima, Peru. Methods: A cross-sectional, analytical observational study was carried out during 2021–2022. Two hundred and ten orthodontists and pediatric dentists were surveyed using the adapted and validated Spanish translation of the OSAKA-KIDS questionnaire and additional sociodemographic questions. Results: The data indicated an association between dental specialty and the professional’s knowledge about POSA. Orthodontists were 59% less likely to have acceptable knowledge, compared to pediatric dentists (p =.013, IC 95% 0.21–0.83). The study revealed an association between the professional’s attitudes and three intervening variables: age (p =.025), clinical experience (p =.049) and sector of practice (p =.020). Conclusion: Knowledge was associated with the dental specialty of professionals in the sample included, whilst attitudes were not.